Luminescent silicon-based nanocarrier for drug delivery in colorectal cancer cells. (October 2020) - Marcelo, Gonçalo A.; Montpeyo, David; Novio, Fernando; Ruiz-Molina, Daniel; Lorenzo, Julia; Oliveira, Elisabete
Abstract: Nanocarriers sensitive to exogenous or endogenous stimuli emerged as an attractive alternative to target drug delivery, with inorganic silica mesoporous nanoparticles (MNs) playing a core role in the development of a new generation of non-toxic and tuneable nanocarriers. A sensitive nanovector (NANO1) comprising luminescent silicon quantum dots (SiQDs) and functionalized with MNs was synthesised and loaded with doxorubicin (DOX). NANO1 nanoparticles have a size of 74 ± 10 nm and DOX loading percentages of ca. 43%. As a control sample, a similar nanocarrier (NANO2), without SiQDs, was also synthesised and loaded with DOX. Release profile studies, in PBS, revealed the strong NANO1 @DOX pH-dependant behaviour, with a pH 5.0 favouring the release of DOX to percentages of ca. 70%. Cytotoxicity assessments of both free and DOX-loaded nanocarriers were evaluated in human cell lines of colon, revealing both free drug and drug-loaded nanoparticles to be concentration-dependent. Graphical abstract: Image 1 Highlights: A Luminescent silicon-based sensitive nanocarrier was synthetized under mild conditions and characterized. The luminescent non-toxic luminescent nanocarriers (NANO1 and NANO2 ) were loaded with Doxorubicin and toxicologically tested in colon human cell lines (HTC116 and HT29). The luminescence properties of these nanomaterials allowed their internalisation into HT29 cancer cells. NANO1 @DOX revealed a pH-dependent behaviour with release percentage of ca. 70%.